Engagement, gender, and motivation: A predictive model for Japanese young language learners. (April 2017) - Oga-Baldwin, W.L. Quint; Nakata, Yoshiyuki
Abstract: A culture of engagement may help to build and sustain young children's motivation to learn a new language. In this study, we sought to investigate the link between engagement and motivation over the course of a semester in a naturally occurring Japanese elementary school classroom environment. Four-hundred and twenty-three fifth-year students in public elementary schools in western Japan agreed to participate in the research. Students completed surveys at two time points, first at the beginning of the semester regarding their in-class engagement, and again at the end of the semester regarding their motivation. A structural equation model was constructed using engagement and gender as predictors and motivational regulations as outcome variables. Observer rating of each class was used to triangulate. Engagement strongly predicted more adaptive intrinsically regulated motives and negatively predicted more extrinsic motives. Male students showed a tendency toward lower engagement, lower internally regulated motives, and higher externally regulated motives. Observer rating showed that students' reported engagement was visible to outside observers. Findings indicate that students' in-class engagement may be an important variable when investigating the long-term dynamics of foreign language learning in a classroom setting. Practical and theoretical implications are discussed.